Descriptive Characterization of Psycho-Trauma, Psychological Distress, and Post-traumatic Stress Disorder among Children and Adolescent Internally Displaced Persons in Kaduna, Nigeria - Sheikh, Taiwo Lateef; Mohammed, Abdulaziz; Eseigbe, Edwin; Adekeye, Tosin; Nuhu, Folorunsho Tajudeen; Lasisi, Modupe; Muhammad, Asiya; Sulaiman, Zainab Titilope; Abdullateef, Aishatu Abubakar; Hayyatudeen, Nafisatu; Akande, Yusuf (Frontiers in Psychiatry, 2016)
Background A postelection violent conflict in Kaduna resulted in 800 deaths and 65,000 displaced people leading to setting up of camp for internally displaced persons (IDPs). We set out to determine the prevalence and pattern of psycho-traumatic stressful life events, psychological distress, and post-traumatic stress disorder (PTSD) among child/adolescents IDPs. Methods A descriptive cross-sectional study of 73 child/adolescent IDPs were selected by total sampling. Stressful life event checklist measured conflict-related trauma and reaction of adolescents to traumatic stress (RATS) measured post-trauma reaction of children/adolescents. Hopkins Symptoms Checklist 37 for Adolescents measured psychological distress associated with trauma. Diagnostic Interview Schedule for Children was used for diagnosis of PTSD. Results Of 73 respondents, 3 (4.1%) had probable PTSD, 2 (2.7%) had definitive PTSD, and mean score of the child/adolescent IDPs on HSCL-37A and RATS was 44.7 (SD = 6.3) and 31.9 (SD = 5.7), respectively. Most frequently occurring psychological distress among female participants was suddenly scared for no reason 7 (19.5%) and becoming angry easily and feeling fearful 5 (13.9%). The average score for female participants were higher than that for males on depressive and anxiety subscale of HSCL-37A. Conclusion We concluded that children/adolescent IDPs were exposed to psycho-trauma following postelection violent conflict and developed psychological distress. However, the low prevalence of psychological distress and PTSD suggested that living with parents and psychosocial intervention provided could have led to much lower morbidity.